Non-suicidal self-injury in young adults with and without borderline personality disorder: the role of emotion dysregulation and negative urgency - Schmidt, Carlos; Briones-Buixassa, Laia; Nicolaou, Stella; Soler, Joaquim; Pascual, Juan C.; Vega, Daniel (Anales de Psicología / Annals of Psychology, 2023)
Non-suicidal self-injury (NSSI) is defined as self-inflicted pain, and it is used as a mechanism to alleviate psychological distress. Although NSSI is prevalent in Borderline Personality Disorder (BPD), it is also an increasing concern among college student populations. While emotion dysregulation and negative urgency are associated with NSSI, little is known about which dimensions specifically predict the motivations (NSSI-functions) and frequency of self-harm. The current study explored the relationship between emotion dysregulation, negative urgency, and NSSI in 86 young adults, divided into three groups: college students with NSSI, BPD patients with NSSI, and a healthy control group without NSSI. We conducted multiple regression analyses to predicted NSSI-functions and NSSI-frequency. Non-acceptance of emotions, a specific dimension of emotion dysregulation, uniquely predicted intrapersonal NSSI-functions (e.g., regulating distressing emotions), but not interpersonal NSSI-functions (e.g., communicating distress). Lastly, poor emotion regulation strategies predicted NSSI-frequency only in individuals with high negative urgency, that is, individuals who tend to act impulsively when experiencing negative emotions, but not in those with low negative urgency. Findings shed light on the underlying motivations for engaging in self-injury, and they reveal facets of emotion dysregulation relevant for NSSI treatment.